PERTUMBUHAN BERBAGAI VARIETAS KEDELAI (Glycine max L. Merril) PADA TANAH ULTISOL KABUPATEN ACEH TENGGARA - Syariani Br. Tambunan; Afkar Afkar (Biotik, 2019)
This study aims to determine the growth of various soybean varieties on Ultisol soil, especially on Ultisol soils in Kutacane. The study was conducted in Gulo Village, Darul Hasanah District, Southeast Aceh Regency, Aceh Province with hilly topography, from May to September 2019 at an altitude of 3200 asl. The study used a Non Factorial Randomized Block Design (RBD), with 4 treatment varieties (V) repeated in 4 replications with 63 plants per plot with 7 samples per plot. The plot size  is 3 m x 2 m with 30 x 20 cm spacing. The total number of plants was 1008, while the total number of sample plants was 112 plants. There are 4 soybean varieties: (V1) Anjasmoro, (V2) Dena1, (V3) Deja 1, and  (V4) Detap 1. The parameters observed in this study during vegetative period include plant height at 1, 2, 3, 4, 5, and 6 week after planting. The plant height were measured from the base of the stem to the highest leaf. The result is that each variety has a different response to the environment so that the growth, flowering period, and harvest period are also different on Ultisol soil especially in District of Southeast Aceh.